Data from: Spatial genetic and morphologic structure of wolves and coyotes in relation to environmental heterogeneity in a Canis hybrid zone - Benson, John F.; Patterson, Brent R.; Wheeldon, Tyler J. (Zenodo, 2012)
Eastern wolves have hybridized extensively with coyotes and gray wolves and are listed as a 'species of special concern' in Canada. However, a distinct population of eastern wolves has been identified in Algonquin Provincial Park (APP) in Ontario. Previous Canis studies have not linked genetic analysis with field data to investigate genotype-specific morphology or determine how resident animals of different ancestry are distributed across the landscape in relation to heterogeneous environmental conditions. Accordingly, we studied resident wolves and coyotes in and adjacent to APP to identify distinct Canis types, clarify the occurrence of eastern wolves adjacent to APP, and investigate spatial genetic structure and landscape-genotype associations in the hybrid zone. We documented 3 genetically distinct Canis types that also differed morphologically, corresponding to putative gray wolves, eastern wolves, and coyotes. We also documented a substantial number of hybrid individuals (36%). Breeding eastern wolves were less common outside of APP, but occurred in some unprotected areas. We identified a steep cline extending west from APP where the dominant genotype shifted abruptly from eastern wolves to coyotes and hybrids. The genotypic pattern to the south and northwest was a more complex mosaic of alternating genotypes. We modeled genetic ancestry in response to prey availability and human disturbance and found positive and negative associations between wolf ancestry and 1) moose density and 2) road densities, respectively. Our results clarify the structure of the Canis hybrid zone adjacent to APP and provide unique insight into environmental conditions influencing hybridization dynamics between wolves and coyotes. Bensonetal.CanisHybridZoneMicrosatelliteData Microsatellite Allele data collected from individual wolves, coyotes, and hybrids (each has individual id, data on separate rows) in central Ontario. Bensonetal.CanisHybridZoneLandscapeData Ancestry and environmental data associated with resident wolves, ...